Analysis of Indian New Education Policy for Higher Education System - Kishor Kumar Dash (AG Volumes, 2022)
An education system and policy that is well-planned, decided, and transparent is necessary for the growth of the economic system as well as the development of society. Since ancient times, India has been far and away the most dominant country in the sphere of education. Since ancient times, students in India have had access to higher education in universities. In the years leading up to and after India's independence, the country's educational system saw a number of important changes. During the time when India was under the control of the British, the whole educational system was based on their concept, and they ran India's educational system in the manner that best suited them. After that, when India gained its independence, there were a number of changes made in education, but Macaulay's education system was still used. It is a rule of nature that things will change, and this law applies to the globe as well. However, these changes should be made for the development of society, nation, and the world. The technique comprises of a conceptual debate on emphasising the notion of the national educational policy framework, highlighting different aspects of the policy connected to higher education of NEP 2020, and comparing the new policy to the education policy that is currently in place. The purpose of this research is to emphasise and provide an overview on the historical viewpoint of the education system, as well as different policies, new education policy merits, and compare with existing education policy.